Incidence, prevalence, and predictors of osteoporotic fracture in adult lung transplant recipients - Elisabeth Ng; Shanal Kumar; Eldho Paul; Daniel Bennett; Luisa Rosi; Louise Fuller; Lauren Chiu; Shoshana Sztal-Mazer; Steven Ivulich; Greg Snell; Leon A. Bach; Kathryn L. Hackman (JHLT Open)
Background: As life expectancy following lung transplantation (LT) improves, vulnerability to glucocorticoid-induced osteoporotic fractures is increased. Our institution offers LT recipients protocolized antiresorptive therapy, with zoledronic acid (ZA) used first line. Methods: Adults who underwent LT from January 2012 to December 2018 and survived at least 6 months were retrospectively studied. Coprimary outcomes were incidence, prevalence, and predictors of osteoporotic fractures and major osteoporotic fractures post-LT. Results: Four hundred and five LT recipients (41% female, median age 59 years) had a median follow-up of 4.9 years (interquartile range 3.4-6.7). Osteoporotic fracture prevalence was 12% (n = 49) pre-LT and 15% (n = 60) post-LT. Major osteoporotic fracture post-LT occurred in 11% (n = 45). Antiresorptive therapy was received by 47% pre- and 89% post-LT. On multivariate analysis, risk factors for osteoporotic fracture were pre-LT osteoporotic fracture (hazard ratio (HR) 2.32 (95% confidence interval (CI) 1.09-4.96)), female sex (HR 2.08 (95% CI 1.09-3.94)), glucocorticoid use pre-LT (HR 2.08 (95% CI 1.09-3.99)), and time (months) to first ZA infusion post-LT (HR 1.04 (95% CI 1.01-1.06)). Risk factors for major osteoporotic fracture were pre-LT osteoporotic fracture, female sex, age, and time to first ZA infusion. Conclusion: LT recipients receiving protocolized antiresorptive treatment post-LT had a low incidence of osteoporotic fracture.